Sexual abuse: an overview - Goicochea Elías, José Julio (2020)
In our society, adequate relevance is not taken for what should be a palpitating concern that grows every day. We refer to sexual abuse being understood as that situation in which the person and specifically their privacy are violated, making them sensitive in all possible aspects. This scenario is really unfortunate for those who live it. It is nothing new to find, once again, women inmersed in statistics that explain the amount of abuse against them. It should be noted that minors are one of the vulnerable groups that tend to be linked to this type of action that falls into a serious criminal offense.